Application of Functional Biocompatible Nanomaterials to Improve Curcumin Bioavailability - Li, Ziyun; Shi, Mingfei; Li, Ning; Xu, Ruodan (Frontiers in Chemistry, 2020)
Curcumin is a lipophilic natural product extracted from turmeric and commonly used as a dietary spice. Being multi-functional, curcumin has been proposed in the prevention and treatment of a broad spectrum of diseases. However, due to unsatisfactory aqueous solubility and hence low bioavailability, clinical application of curcumin has been greatly restrained. To break these limitations, biocompatible nanoformulation, such as liposomes, nanoparticles, micelles, nanoemulsions and conjugates has been employed as alternatives to improve in vivo delivery of curcumin. In this scenario, in order to enhance bioavailability of curcumin, the choice of effective molecules as facilitators is of prominence. In this review, we focus on functional biocompatible materials, including polymers, protein molecules, polysaccharide, surface stabilizers and phospholipid complexes, and decipher their potential applications as how they assist to promote medicinal performance of curcumin.